Investigation of Haemoglobin Polymorphism in the Indian Bikaneri Sheep - Adhikari, Alka; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
Haemoglobin polymorphism in the Indian Bikaneri sheep breed in two age-groups, i.e., 1–6 months and 6 months–1 year was investigated. 18.75% Hb A type. 31.25% Hb B type and 50.0% Hb AB types were found. While 0.44 Hb AA and 0.56 Hb BB gene frequencies were observed.